Entry and Expansion Strategies for Burberry in Oman by Applying Porter's Five Forces Model - Abalkhail, Tagreed Saleh (Indian Journal of Marketing, 2019)
The purpose of this study was to apply Michael E. Porter's â€œFive Forcesâ€ analysis to suggest how Burberry should pursue expansion into Oman and to reveal the strengths and weaknesses of the Omani market in terms of luxury brands. By employing Porter's model as the theoretical framework, an extensive review of published literature was conducted for this study. The results showed that several forces lower entry barriers for foreign luxury retailers in Oman, including deregulated policies and few competitors. There are few alternatives for Burberry to reduce the threats of substitutes. The results also showed that the intensity of competitive rivalry is not high in the Omani luxury market. The findings will be useful for the retailers for entering the Omani luxury fashion marketplace and provide an overview of Burberry's expansion into a new market by evaluating the multi-dimension of competition and conditions in Porter's five forces model.